1990
DOI: 10.1083/jcb.111.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cell-free system to study the membrane assembly of photosynthetic proteins of Rhodobacter capsulatus.

Abstract: Abstract. A cell-free translation system from the facultatively photoheterotrophic bacterium Rhodobacter capsulatus is described. Synthesis of two proteins of the bacterium's photosynthetic apparatus (lightharvesting complex B870 ot and/~) was performed by SP6 polymerase transcription of the subcloned genes, isolation of the mRNA and translation in vitro using a cell-free extract of R. capsulatus cells.The integration of these proteins in vitro into added intracytoplasmic membrane vesicles (ICM) is demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…On the other hand, in vitro studies (44) demonstrated that a cotranslational membrane association was more efficient than a posttranslational one, which suggests synthesis on membranebound ribosomes.…”
mentioning
confidence: 99%
“…On the other hand, in vitro studies (44) demonstrated that a cotranslational membrane association was more efficient than a posttranslational one, which suggests synthesis on membranebound ribosomes.…”
mentioning
confidence: 99%
“…the translocation of preLamB, by in-vitro-assembled SecY, provides evidence that in-vitro-synthesized SecY integrates into the lipid bilayer of INV in an enzymically active conformation. Similar assays for the functional integration of invitro-synthesized, bacterial plasma-membrane proteins have recently been described for the lactose permease of E. coli (Ahrem et al, 1989) and the subunits of light-harvesting complex I of Rhodohacter cupsulutus (Troschel and Miiller, 1990).…”
Section: Functional Membrane Integration Of Secy In Vitromentioning
confidence: 99%
“…We have recently described a method which employs sucrose-gradient centrifugation to separate free from membrane-associated integral membrane proteins following in vitro synthesis (Ahrem et al, 1989;Troschel and Miiller, 1990). Fig.…”
Section: In-vitvo-synthesized Secy Associates With Plasma-membrane Vementioning
confidence: 99%
“…We have now cloned, isolated, and characterized SecA of R. capsulatus. The existence of a homologous in vitro system (58,66) to study the translocation activity of SecA enabled us to directly compare SecA of R. capsulatus with that of E. coli. It thereby became evident that the activity of a distinct SecA species depends not only on the target membranes but also exquisitely on the precursor to be translocated.…”
mentioning
confidence: 99%
“…We have started to analyze protein export in Rhodobacter capsulatus (57,58,66,67), which belongs to the group of ␣-subclass purple bacteria. Based on a 16S rRNA sequence analysis (68), these bacteria are closely related to the ancestral prokaryote that, according to the endosymbiont theory, gave rise to mitochondria.…”
mentioning
confidence: 99%